Group Academic Counseling for First Year Student-Athletes - Wilson, Bob (My University, 1985)
This article reviewed a study of eight athletes in a group counseling program (one hour per week for eight weeks) that took place during study hall. The program resulted in increased GPAs amongst participants. Participants also provided responses to an open-ended question about the group counseling program.
Keywords: academic support; skills